Konsep persaingan usaha ditinjau dari etika bisnis Islam - Izzah, Indy Nur (Maliki Interdisciplinary Journal, 2024)
Business competition is often found in the business world, where business actors compete in many things such as product marketing, service to consumers and product quality to be the most popular in a market, basically this has a positive influence on business actors because they are of course will continue to innovate to continue to improve its products, however, a good thing is sometimes misused by some people so that something that was initially good turns into something bad, such as unhealthy business competition. Indonesia has a majority Muslim population, therefore the business competition that will be discussed will be reviewed with Islamic Business Ethics where Islam is a perfect religion so that all the activities of its followers have guidelines for carrying them out and for people who obey these guidelines will certainly be safe people. in this world and in the afterlife. The research used in this journal is juridical-normative research using various journal literature (literature studies) as the main data. The results of this research show that there is a connection between business competition and Islamic business ethics, where Islamic business ethics teaches business actors to do good things, including conducting business competition.